Effects of newly harvested corn on growth performance, intestine development and metabolism of nutrients in broilers - Guang Zhong (Italian Journal of Animal Science, 2019)
This experiment was to study the effects of newly harvested corn on growth performance, intestine development and metabolism of nutrients in broilers. A total of 380 one-day-old Arbor Acres male broilers were assigned to ageing corn group (AC group), 1/3 newly harvested corn group (1/3 NC group), 2/3 newly harvested corn group (2/3 NC group), and newly harvested corn group (NC group), which according to the proportion of newly harvested corn in the total amount of corn of basal diets. Each group included six replicates with 16 birds. Digestion and metabolism trials were conducted at 39 to 42 days of age. Results showed that feed: gain ratio (F/G) of NC group was higher than that of 1/3 NC group and 2/3 NC group at 22 to 42 and 1 to 42 days of age (p < .05). The metabolic rates of calcium and phosphorus in NC group were lower than those in AC group, 1/3 NC group and 2/3 NC group (p < .05). In NC group, the relative weight of caecum was significantly higher than that in 2/3 NC group and AC group at 21 days of age (p < .05), while the relative weight of jejunum was lower than that in 2/3 NC group and AC group at 42 days of age (p < .05). In summary, newly harvested corn can reduce the growth performance and metabolism of some nutrients in broilers. Newly harvested corn should be controlled during actual production.Highlights Newly harvested corn can reduce the growth performance in broilers. Newly harvested corn can reduce apparent metabolic rate of calcium and phosphorus in broilers. Newly harvested corn can affect the intestine development in broilers.